Riemann Integral Construction Of A Sequence Of Functions In A Normed Space (l^p,‖∙‖_p ) - Aswad Hariri Mangalaeng; Naimah Aris; Jusmawati Massalesse (Department of Mathematics, Hasanuddin University, 2020)
We construct Riemann Integral for a sequence in a normed space (l^p,‖∙‖_p ). To do construction, we used some theories of real analysis and functional analysis, include some real sequences theories, some Riemann integral theory for functions in R, and some norm theories in a normed space (l^p,‖∙‖_p ). In this paper, we otained that a sequence of functions f=(f_k ):[a,b]⊂R→l^p qualify that the sequence is Riemann integrable on [a,b]⊂R.